Effect of Water in the Synthesis of Nano BaTiO3 Particle Using Potassium Hydroxide - Park, Kug-Hyo; Gu, Sin-Il; Shin, Hyo-Soon; Yeo, Dong-Hun; Kim, Hyung-Sun; Ha, Gook-Hyun (Asian Journal of Chemistry, 2013)
The synthesis conditions of low reaction temperature and normal pressure must be satisfied to improve dispersion and to facilitate the control of nano particle size. Based on this, the low temperature synthesis conditions of nano BaTiO3 particles were investigated using the molten salt method. Nano BaTiO3 particles were synthesized using KOH and KOH-KCl and the results of the different types of salt were compared. The potential synthesis at low temperature was also assessed according to the addition of water. The nucleation of BaTiO3 particles and growth of particles were promoted in the case of KOH-KCl compared to that of KOH. In the case of the KOH-KCl, sufficient phase synthesis was observed at 200 ºC, which is lower than the melting point of salt of 401 ºC. With the addition of water, phase synthesis occurred among the nano BaTiO3 particles at over 120 ºC in a 7.6 M salt solution. This is thought to be caused by the increased solubility of salt due to the salting-in effect.